EFEITO DA SUBSTÂNCIA APAZIGUADORA BOVINA (SAB) SOBRE A PERFORMANCE À IATF E DESEMPENHO PRODUTIVO DE NOVILHAS NELORE - MACHADO, João Victor Bezerra,; DA SILVA, Aldair Félix,; CORDEIRO, Dauydison Antônio Gonzales,; DA SILVA, Millena Vitória,; STERZA, Fabiana de Andrade Melo,; SOUZA, Andréa Roberto Duarte Lopes, (ANAIS DO ENIC, 2024)
-